Impact of acute kidney injury in deceased donors with high Kidney Donor Profile Index on posttransplant clinical outcomes: a multicenter cohort study - Woo Yeong Park; Yoon Kyung Chang; Young Soo Kim; Kyubok Jin; Chul Woo Yang; Seungyeup Han; Byung Ha Chung (The Korean Society of Nephrology, 2021)
Background This study evaluated the impact of acute kidney injury (AKI) on posttransplant clinical outcomes for deceased donor (DD) kidney transplantation (KT) using the Kidney Donor Profile Index (KDPI) system. Methods Overall, 657 kidney transplant recipients (KTRs) receiving kidneys from 526 DDs from four transplant centers were included. We divided them into the high and low KDPI donor groups by 65%, the KDPI score, and both groups were subdivided into the AKI-DDKT and non-AKI-DDKT subgroups according to AKI in DDs. Results There was no significant difference in the incidence of delayed graft function (DGF) between the high and low KDPI-KTR groups; however, the AKI-DDKT subgroup showed significantly higher incidence of DGF than the non-AKI-DDKT subgroup in both groups (p = 0.001, p < 0.001, respectively). The death-censored graft survival rate was significantly lower in the high KDPI-KTR group than in the low KDPI-KTR group (p = 0.005). Only in the high KDPI-KTR group, the death-censored graft survival rate was significantly lower in the KT from DDs with AKI stage 3 than KT from DDs with non-AKI or AKI stage 1 or 2 (p = 0.040). The interaction between AKI stage 3 in DDs and high KDPI on the allograft outcome was significant (p = 0.002). Conclusion KTs from DDs with AKI stage 3 showed an adverse impact on the allograft outcome in the high KDPI-KTR group. Therefore, DDs with a high KDPI score should be managed carefully so that severe AKI does not occur prior to KT.